Doppler echocardiographic examinations in the assessment of the athletic heart - Pavlik, G.; Olexo, Z.; Sido, Z.; Frenkl, R. (Acta Physiologica Hungarica, 1999)
Doppler echocardiography is a method with the help of which flow velocity and the duration of different intervals can be estimated. The ratio between early and late peak velocities (E/A) is linearly proportional to diastolic function, i.e. to ventricular compliance. Data of 179 athletes and of 42 nontrained young healthy men indicated that the E/A quotient was higher in athletes than in the sedentary controls (2.086 +/- 0.505 vs. 1.905 +/- 0.384) in young adult age, but of the different athletes it was the only group of endurance athletes that showed a significant increase. Regular physical training seems to protect against an age-dependent impairment of left ventricular compliance, as an increased E/A ratio can be observed at the age of 31-45 years (1.77 +/- 0.46 vs. 1.43 +/- 0.276) as well as in men above 45 years of age (1.61 +/- 0.36 vs. 1.24 +/- 0.36). Bradycardia of the athletic heart resulted in a significantly longer duration of the cardiac cycle in athletes than in non-athletes. Different phases of the cardiac cycle, however, were not equally modified. There were periods the absolute duration of which were slightly decreased, unchanged or slightly increased, but the relative ones are strongly decreased: such as isovolumetric contraction time (ICT), acceleration of the transaortic flow (AOAT), deceleration of the transaortic flow (AODT), acceleration period of the early diastolic filling (EACC), and deceleration period of the early diastolic filling (EDT). There were periods the absolute duration of which increased proportionally to the increase of the whole cardiac cycle, while relative duration was not changed: isovolumetric contraction time (IVRT) and the atrial systole (A). There was one period that showed the greatest variability in the different subjects and both its absolute and relative duration was definitely increased in the athletes: this was the EA period, i.e. the period from the end of early filling to the beginning of the atrial systole.